The Innovativeness of Bio-Pharmaceutical Cluster or Import Substitution: the Development Priorities of the Economy Sector - Alexander Nickolaevich Tsatsulin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The authors analyze the complex problems associated with the formation of regional industrial clusters of really innovative type, with the introduction into the activities of the real economy scheme of public-private partnership, with the revival of the national pharmaceutical industry, in particular pharmaceutical industry. Solution of these problems, according to the authors, provide a procedure for import of foreign drugs quality Russian pharmaceuticals, which is currently the most important problems facing the society and the state. Degradable materials demonstrate the relevance of the issues raised in the article. The authors consider the pharmaceutical cluster of St. Petersburg, activities, participants, members of these relatively new form of territorial units, analyze the innovative activity of a number of existing companies a bearing producing both generic and original commercial products with innovative features. To identify innovative leaders in the cluster technique used multidimensional comparative analysis. The end of the article contains the conclusions and the proposals.